2020
DOI: 10.1021/acs.jpcc.0c03661
|View full text |Cite
|
Sign up to set email alerts
|

New Pigeonholing Approach for Selection of Solvents Relevant to Lead Halide Perovskite Processing

Abstract: Intensive development of solution deposition methods for perovskite solar cell fabrication requires rational optimization of existing methods and search for new effective solvents of different origin involved in key stages of the techniques. We propose a novel approach for rational solvent selection predetermining the character of their interaction with lead halide perovskites in terms of the analysis of donor numbers, dipole moments, and Hansen hydrogen bonding parameters. Experimental proof of the proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…The presence of PbI 2 -like inclusions in type-B stacking faults, theoretically predicted above, could be derived from the structure of lead iodide complexes in perovskite solution. It is known that DMF solvent tends to form coordination complexes with PbI 2 , where PbI 6 octahedra are connected predominantly by edges or faces, leading to the formation of polynuclear complexes (the "building blocks") [32,33]. Incorporation of such building blocks into the LHHPs crystal structure during thin film crystallization may promote the formation of stacking faults with a shift value of t = 1/2 (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of PbI 2 -like inclusions in type-B stacking faults, theoretically predicted above, could be derived from the structure of lead iodide complexes in perovskite solution. It is known that DMF solvent tends to form coordination complexes with PbI 2 , where PbI 6 octahedra are connected predominantly by edges or faces, leading to the formation of polynuclear complexes (the "building blocks") [32,33]. Incorporation of such building blocks into the LHHPs crystal structure during thin film crystallization may promote the formation of stacking faults with a shift value of t = 1/2 (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28] An intricate interplay between solubility, polarity, dielectric screening, and coordinating ability has been accounted responsible for the efficacy of different solvents to form complexes with LHPs. [20,21,29] Furthermore, the choice of the solvent turned out to be a critical parameter for the formation of intermediate phases [19,[30][31][32][33][34] and even for the creation of defects in the final products. [35,36] This vast body of experimental research has been supported by theoretical and computational work.…”
Section: Introductionmentioning
confidence: 99%
“…While the crystal lattice energy of the perovskites increases in the series MAPbI 3 -MAPbBr 3 -MAPbCl 3 according to the experimental thermodynamic data [13], the intensity of the interaction of solvent molecules with Pb 2+ ions can be described by donor numbers (DN), as it was shown in [12]. The donor number is determined on the basis of the experimental enthalpies of complexation with a strong electron-pair acceptor SbCl 5 , defined for the chosen solvents as DN(GBL) = 18.0, DN(DMF) = 26.6 and DN(DMSO) = 29.8 [14].…”
Section: Resultsmentioning
confidence: 90%
“…The configurations of solvated iodoplumbate complexes in DMSO and DMF solutions of MAPbI 3 were modeled in [10,11]. In 2020, Tutantsev et al proposed a model explaining the interaction and relative solubility of hybrid perovskites in different solvents and showed that it relies on strong donor−acceptor, ion−dipole and hydrogen bonding interactions which can be described by donor numbers, dipole moments and Hansen hydrogen bonding parameters, respectively [12].…”
Section: Introductionmentioning
confidence: 99%